Nanohydroxyapatite-Blasted Bioactive Surface Drives Shear-Stressed Endothelial Cell Growth and Angiogenesis. (23rd February 2022) - Pinto, T. S.; Martins, B. R.; Ferreira, M. R.; Bezerra, F.; Zambuzzi, W. F.
Abstract : Nanosized crystalline hydroxyapatite coating (HAnano®) accelerates the osteointegration of dental implants which is hypothesized to drive angiogenesis. In order to test this hypothesis, we have subjected shear-stressed human umbilical vein endothelial cells (HUVECs) to a HAnano®-enriched medium, as well as to surface presenting dual acid etching (DAE) as a control. To note, the titanium implants were coated with 10 nm in diameter HA particles using the Promimic HAnano method. Our data reveals that HAnano® modulates higher expression of genes related with endothelial cell performance and viability, such as VEGF, eNOS, and AKT, and further angiogenesis in vitro by promoting endothelial cell migration. Additionally, the data shows a significant extracellular matrix (ECM) remodeling, and this finding seems developing a dual role in promoting the expression of VEGF and control endothelial cell growth during angiogenesis. Altogether, these data prompted us to further validate this phenomenon by exploring genes related with the control of cell cycle and in fact our data shows that HAnano® promotes higher expression of CDK4 gene, while p21 and p15 genes (suppressor genes) were significantly lower. In conjunction, our data shows for the first time that HAnano®-coated surfaces drive angiogenesis by stimulating a proliferative and migration phenotype of endothelial cells, and this finding opens novel comprehension about osseointegration mechanism considering nanosized hydroxyapatite coating dental implants.